Comparison of CBCT Prescriptions among Different Campuses of East Carolina University School of Dental Medicine - Cody C. Phen; Gerard A. Camargo; Wenjian Zhang (International Journal of Dentistry)
Objectives. East Carolina University School of Dental Medicine (ECU SoDM) has established a unique education model that delivers the dental curriculum through student rotations at community service learning centers (CSLCs) in underserved areas across North Carolina in their senior year. The objective of the study is to analyze the patient composition and CBCT prescription patterns at the main campus (Ross Hall) and eight CSLCs, to determine if students have comparable training at various sites. Methods. CBCTs taken at ECU SoDM in 2017–2021 were evaluated. One-way analysis of variance and the Wilcoxon Rank Sum Test were used to determine any differences in demographics, Medicaid coverage, and scan indications at various sites. Results. A total of 1444 patients were included, with an age range of 4–90 years old; male 685, female 758; 1130 non-Hispanic/Latino, 71 Hispanic/Latino. For races, Caucasian 1106, African-American 156, American Indian/Alaskan Native 32, Asian 18, mixed 13, other 73. For Medicaid, there are 75 with and 1369 without coverage. Ross Hall has the largest amount of patients at 537, followed by Davidson 218, Brunswick 189, and Lillington 169, with Elizabeth City being the least with 45 patients. The top four reasons for taking CBCTs were implants, endodontics, oral pathology, and 3rd molar assessment. There was no significant difference in the indications for CBCTs or Medicaid coverage, among various sites. Conclusions. The demographics, Medicaid coverage and CBCT prescription patterns were comparable among various sites. There was a site-related difference in the amount of scans taken, warranting the necessity to monitor CSLC rotation selections to ensure a consistent learning experience.